Saccharification and fermentation of the lignocellulosic residues of the orange to obtain bioalcohol - Alcívar-Mendoza, Pablo Enrique; Muñoz-Murillo, José Patricio; Andrade-Díaz, Christhel Alejandra; Dueñas-Rivadeneira, Alex Alberto (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
The production and consumption of oranges generates a large amount of lignocellulosic waste that is deposited in landfills without receiving any type of treatment that allows it to be used as by-products. The objective of the present investigation was to obtain bioalcohol through the saccharification and fermentation of lignocellulosic residues of the peel of the orange (Citrus sinensis). Three (3) different levels of sulfuric acid were used as treatment, to alter the lignocellulosic structure of the biomass, subsequently, a hydrolysis with cellulase enzymes was carried out, analyzing the presence of reducing sugars by spectrophotometry. The fermentation was carried out with two (2) different concentration levels of Sacharomyces cerevisiae yeast, subsequently, it was distilled and the presence of volatile organic compounds was determined by gas chromatography. The reducing sugars present in the highest proportion were: glucose (26.6 ± 0.77 g.L-1) and fructose (21.26 ± 0.51 g. L-1); the volatile organic compound with the highest concentration was ethanol (76.96%) and the index with the highest bioalcohol yield was obtained with the treatment with the highest concentration of sulfuric acid and yeast (12.72 ± 0.65 g. L-1); Orange peels are by-products of vegetable origin that can be used for the production of bioalcohol with percentages of ethanol higher than 76%.